A Sensitive Reversed-phase High‑performance Liquid Chromatography Method for the Analysis of Eplerenone - Annapurna, Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Eplerenone is an anti-hypertensive drug. A sensitive reversed-phase high-performance liquid chromatography method was developed for the assay of Eplerenone (Isocratic mode) in the presence of an internal standard, teneligliptin (an antidiabetic drug). Materials and Methods: Mobile comprising formic acid and methanol was selected (flow rate: 0.4 ml/min), and Eplerenone as well as the internal standard were eluted a detection wavelength of 244 nm. Phenomenex C8 column was used during the study, and the HPLC system was from Shimadzu with photodiode array detector. Results and Discussion: Eplerenone follows linearity according to Beer–Lambert’s law 0.5–60 μg/mL with regression equation, y = 0.2054x + 0.0351 correlation coefficient 0.9996. The LOD and LOQ are found to be 0.0141 μg/mL and 0.3947 μg/mL, respectively. Conclusions: The liquid chromatographic method is simple and sensitive, and the method was validated for the determination of Eplerenone in pharmaceutical dosage forms.